A note on hyperbolically embedded subgroups. Issue 4 (3rd April 2022) - Martínez-Pedroza, Eduardo; Rashid, Farhan
Abstract: Let G be a group and H a subgroup of G . The notion of H being hyperbolically embedded in G was introduced by Dahmani, Guiraldel, and Osin. This note introduces an equivalent definition of hyperbolic embedded subgroup based on Bowditch's approach to relatively hyperbolic groups in terms of fine graphs.